Laparoendoscopic Single-Site Nephrectomy Using Standard Laparoscopic Instruments: Our Initial Experience - Aminsharifi, Ali Reza; Goshtasbi, Bahman; Afsar, Firoozeh (Urology Journal, 2012)
PURPOSE: To report our initial experience with laparoendoscopic single-site (LESS) nephrectomy using a GelPOINT single port and standard laparoscopic instruments. MATERIALS AND METHODS: Laparoendoscopic single-site transperitoneal nephrectomy was done for 6 adult patients with a poorly functioning small or hydronephrotic kidney. The procedure was done with the GelPOINT system, which consisted of a wound retractor (Alexis) and GelSeal cap. Standard laparoscopic instruments were used and the renal pedicle was controlled with 10-mm Hem-o-Lok clips. RESULTS: The participants were 3 men and 3 women with the median age of 29.5 years. Laparoendoscopic single-site nephrectomy was successfully done in all the patients without any major complications. Median operation time was 110 minutes (range, 90 to 130 minutes). There was no need for blood transfusion in any patient. The recovery phase was uneventful and all the patients were discharged after a median hospital stay of 2.5 days (range, 2 to 3 days). Renal function remained stable in all the patients after the operation. The incision site healed well on postoperative follow-up. CONCLUSION: Our initial experience with LESS nephrectomy was successful with the use of a GelPOINT single port and standard laparoscopic instruments. This report may remove barriers to further work with the LESS technique and may offer a strategy to help surgeons gain experience with this novel technology.